The Agronomey of Soil Conservation - WHYTE, R O (Journal of Soil and Water Conservation, 2022)
Let us assume that a given land area has been classified for proper use in relation to climate, erodibilitv of soil and degree of slope, and that the soil conser-vation engineer has laid out the necessary terraces, blinds, water disposal systems and so on. It then becomes the job of the agronomist to introduce those measures which will ensure the success of the operation on a long-term basis. lie will have been told that certain slopes may safely be used for the cultivation of arable crops in rotation systems, that others should be kept under a permanent grass cover, that the steepest should remain under trees for the produc-tion of fruits, nuts, tree fodder, fuel wood or timber.